Functional programming in JavaScript - Atencio, Luis, ....- (Shelter Island : Manning, 2016)
"Functional Programming in JavaScript teaches JavaScript developers functional techniques that will improve extensibility, modularity, reusability, testability, and performance. Through concrete examples and jargon-free explanations, this book teaches you how to apply functional programming to real-life development tasks"--Publisher's web site.
Part 1: Think functionally. Becoming functional ; Higher-order JavaScript -- Part 2: Get functional. Few data structures, many operations ; Towards modular, reusable code ; Design patterns against complexity -- Part 3: Enhancing your functional skills. Bulletproof your code ; Functional optimizations ; Managing asynchronous events and data.
Includes index.
Keywords: JavaScript (Computer program language).; Functional programming (Computer science).; Functional programming (Computer science).; JavaScript (Computer program language).